Incidental Adrenal Nodules in Patients Without Known Malignancy: Prevalence of Malignancy and Utility of Washout CT for Characterization-A Multiinstitutional Study - Corwin, Michael T; Badawy, Mohamed; Caoili, Elaine M; Carney, Benjamin W; Colak, Ceylan; Elsayes, Khaled M; Gerson, Rosalind; Klimkowski, Sergio P; McPhedran, Rachel; Pandya, Amit; Pouw, Matthew E; Schieda, Nicola; et al. (American journal of roentgenology (1976), 2022)
Washout CT is commonly used to evaluate indeterminate adrenal nodules, although its diagnostic performance is poorly established in true adrenal incidentalomas. The purpose of this study was to compare, in patients without a known malignancy history, the prevalence of malignancy for incidental adrenal nodules with unenhanced attenuation more than 10 HU that do and do not show absolute washout of 60% or more, thereby determining the diagnostic performance of washout CT for differentiating benign from malignant incidental adrenal nodules. This retrospective six-institution study included 299 patients (mean age, 57.3 years; 180 women, 119 men) without known malignancy or suspicion for functioning adrenal tumor who underwent washout CT, which showed a total of 336 adrenal nodules with a short-axis diameter of 1 cm or more, homogeneity, and unenhanced attenuation over 10 HU. The date of the first CT ranged across institutions from November 1, 2003, to January 1, 2017. Washout was determined for all nodules. Reference standard was pathology ( = 54), imaging follow-up (≥ 1 year) ( = 269), or clinical follow-up (≥ 5 years) ( = 13). Prevalence of malignancy among all nodules, nodules less than 4 cm, and nodules 4 cm or more was 1.5% (5/336; 95% CI, 0.5-3.4%), 0.3% (1/317; 95% CI, 0.0-1.7%), and 21.1% (4/19; 95% CI, 6.1-45.6%), respectively. Prevalence of malignancy was not significantly different for nodules smaller than 4 cm with (0% [0/241]; 95% CI, 0.0-1.2%) and without (1.3% [1/76]; 95% CI, 0.0-7.1%) washout of 60% or more ( = .08) or for nodules 4 cm or larger with (16.7% [1/6]; 95% CI, 0.4-64.1%) and without (23.1% [3/13]; 95% CI, 5.0-53.8%) washout of 60% or more ( = .75). Washout of 60% or more was observed in 75.5% (243/322; 95% CI, 70.4-80.1%) of benign nodules (excluding pheochromocytomas), 20.0% (1/5; 95% CI, 0.5-71.6%) of malignant nodules, and 33.3% (3/9; 95% CI, 7.5-70.1%) of pheochromocytomas. For differentiating benign nodules from malignant nodules and pheochromocytomas, washout of 60% or more had 77.5% sensitivity, 70.0% specificity, 98.8% PPV, and 9.2% NPV among nodules smaller than 4 cm. Prevalence of malignancy is low among incidental homogeneous adrenal nodules smaller than 4 cm with unenhanced attenuation more than 10 HU and does not significantly differ between those with and without washout of 60% or more; wash-out of 60% or more has suboptimal performance for characterizing nodules as benign. Washout CT has limited utility in evaluating incidental adrenal nodules in patients without known malignancy.